Dor Crónica Lombar: Incapacidade Auto Reportada em Trabalhadores do Sector da Saúde e sua Relação com Fatores Psicossociais e Intensidade da Dor - Rodrigues, Carlos (2012)
Objective: To examine the association between pain catastrophizing, fear avoidance beliefs and intensity of pain with self reported functional disability in patients with chronic low back pain. Methods: An observational analytic cross-sectional sample of 90 individuals with chronic low back pain. Data collection was conducted through the following four measures: Questionnaire for QCLI survey variables, the Roland Morris,Disability Questionnaire; the pain catastrophizing scale; and the fear avoidance beliefs questionnaire. Data analysis was performed using the frequency distribution and measures of central tendency and the nonparametric correlation test of Spearman. Results: The pain catastrophizing variable obtained a correlation value with the self reported disability rs = 0.446, p <0.01, the variable of fear avoidance beliefs of work-related pain obtained a correlation value with the self reported disability rs = 0.455 to p <0.01, current pain intensity and in the previous year obtained values of correlation with selfreported disability rs = 0.289 and rs = 0.362 respectively for p-value <0.01. Conclusion: The psychosocial variables of pain catastrophizing and fear avoidance belief of pain-related to work, have a moderate association with disability in individuals with chronic low back pain. The association between pain intensity and disability seems to have a less important role demonstrating low associations.